Pendidikan Karakter Berbasis Riyadhoh TQN Suryalaya dalam Perspektif KH. A. Shohibul Wafa Tajul ‘Arifin ra. (Abah Anom) - Kusmana, Ratna; Suhrowardi; Kurniawan, Ase (Prodi PAI IAILM Suryalaya, 2025)
This study aims to identify and analyze the implementation of character education based on riyadhoh in the Qadiriyah Naqsyabandiyah Order (TQN) Suryalaya according to Abah Anom's view. The research method used is qualitative research with data collection techniques using observation, interview and documentation techniques. Observations were conducted to directly see the amaliyah riyadhoh applied at the Suryalaya Islamic Boarding School, while interviews were conducted with ikhwan akhwat or students, as well as figures who understand the teachings of Abah Anom. Documentation is used to collect data from various written sources, such as books, articles, and official documents of Islamic boarding schools. The results of the study indicate that riyadhoh-based character education at TQN Suryalaya includes spiritual training and special practices aimed at getting closer to Allah SWT, improving morals, and forming a strong personality. Riyadhoh taught by Abah Anom includes dhikr, khotaman, manaqiban, pilgrimage, fasting, qiyamullail, and various other forms of worship that are carried out consistently and carried out under the guidance of a mursyid. The implementation of this character education has a positive impact on the formation of the character of students, such as increasing patience, honesty, discipline, and responsibility. From the results of observations and interviews, character education through riyadhoh amaliyah activities has been applied well and in accordance with applicable regulations, although there are several obstacles for brothers and sisters who still deviate in their behavior, but can be minimized so that the morals of students have seen an increase after participating in riyadhoh activities, namely in terms of behaviour, words and deeds. This study provides results that riyadhoh in TQN Suryalaya in Abah Anom's perspective is not only a spiritual practice, but also an effective method in character education that is able to shape ikhwan akhwat into individuals with noble morals and strong personalities.